Upaya Pemberdayaan Keluarga Melalui Program Workshop Bina Masyarakat Dalam Meningkatkan Kesadaran Beragama Di Desa Kondangjajar - Dede Nurul Qomariah; Taufik Hidayat; Dedeh Nurdiah; Nendi Sahrul Mujahid; Anja Sugiarti; Mansur Nasrulloh; Ratmi Ratmi (Institut Teknologi dan Bisnis Semarang, 2023)
The efforts to empowering families in Kondangjajar Village through this community development workshop program aim to increase religious awareness in Kondangjajar Village, especially for vulnerable teenagers aged 13-17 years. Collaborative cooperation between families, communities and local government in creating religious awareness among teenagers in Kondangjajar Village is an important thing to do. This community service was carried out in Kondangjajar Village, Cijulang District, Pangandaran Regency in August 2023. The method used in this service is the participatory action research (PAR) method, where this method focuses on colaborative problem solving between academics, the community and the local government. Problem identification is carried out qualitatively. The problems found are created on a priority scale and discussed by the service team, community leaders and the local village government to design the service program that will be implemented. The results of the service found that efforts to empowering families through community development workshop programs in increasing religious awareness in Kondangjajar village were able to provide strengthening for the community.